Output Collapse in Eastern Europe : The Role of Credit - Calvo, Guillermo (IMF Working Papers; Working Paper ;, 1992)
Real bank credit in Eastern European countries after their recent stabilization programs is shown to have fallen sharply, except in the case of Hungary. The meaning of the fall is discussed under the present value and liquidity perspectives. Moreover, it is shown that the hypothesis that output contraction may be partly due to credit contraction cannot be ruled out. The hypothesis is tested on a sample of 85 branches of industry in Poland. The rationale for expecting a connection between credit and output and policy options to attenuate the liquidity crunch in post-socialist economies is also subject to analysis.